1993
DOI: 10.3109/02713689308999485
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin does not increase IOP significantly in rabbits

Abstract: New Zealand white rabbits have a circadian rhythm of intraocular pressure; pressure is higher during the dark than during the light. We explored the possibility that the dark phase increase of serum and/or ocular melatonin plays a role in regulating the rhythm of intraocular pressure. Exogenous melatonin was delivered by four routes: topical application (0.1 and 10 micrograms), intravenous injection (1 microgram), intravitreal injection (9 micrograms) and intra-arterial infusion (50 ng and 1 microgram). Melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
4
2
Order By: Relevance
“…In contrast, it has been demonstrated that oral or topical administration of melatonin reduces IOP in monkeys, rabbits, and humans . However, other studies did not find any effect of topical application, intravenous or intravitreal injection, and intra‐arterial infusion of melatonin on rabbit IOP . In addition, we have previously shown that the administration of melatonin as a subcutaneous pellet does not affect IOP in normal or glaucomatous rats .…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In contrast, it has been demonstrated that oral or topical administration of melatonin reduces IOP in monkeys, rabbits, and humans . However, other studies did not find any effect of topical application, intravenous or intravitreal injection, and intra‐arterial infusion of melatonin on rabbit IOP . In addition, we have previously shown that the administration of melatonin as a subcutaneous pellet does not affect IOP in normal or glaucomatous rats .…”
Section: Discussioncontrasting
confidence: 67%
“…44 However, other studies did not find any effect of topical application, intravenous or intravitreal injection, and intra-arterial infusion of melatonin on rabbit IOP. 45,46 In addition, we have previously shown that the administration of melatonin as a subcutaneous pellet does not affect IOP in normal or glaucomatous rats. 26 Although we do not have any explanation for this discrepancy, differences in species, administration route, and dose, as well as the particular ocular condition (eye submitted to PE), could account for it.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of melatonin on IOP is still controversial. Several studies did not find any effect of topical application, intravenous or intravitreal injection, and intraarterial infusion of melatonin on rabbit IOP [39, 40], whereas other groups have demonstrated that oral or topical administration of melatonin reduces IOP in rabbits [41], monkeys [42], and humans [43]. In our experimental setting, a subcutaneous pellet of melatonin did not change IOP along 10 wk of treatment with HA.…”
Section: Discussioncontrasting
confidence: 50%
“…Baseline IOP using applanation tonometry has been determined for many species of animals, including dogs, cats, raptors, horses, ponies, dairy cows, ferrets, Nubian ibexes, Grant zebras, Arabian oryxes, rabbits, rats, alligators, and lions; 6 –17 however, to our knowledge a controlled study measuring baseline IOP in llamas and alpacas has not been reported.…”
Section: Discussionmentioning
confidence: 99%